Ultra-fine pitch palladium-coated copper wire bonding : effect of bonding parameters - Lim, Adeline B. Y. (2014)
Copper (Cu) wire bonding has become a mainstream IC assembly solution due to its significant cost savings over gold wire. However, concerns on corrosion susceptibility and package reliability have driven the industry to develop alternative materials. In recent years, palladium-coated copper (PdCu) wire has become widely used as it is believed to improve reliability. In this paper, we experimented with 0.6 ml PdCu and bare Cu wires. Palladium distribution and grain structure of the PdCu Free Air Ball (FAB) were investigated. It was observed that Electronic Flame Off (EFO) current and the cover gas type have a significant effect on palladium distribution in the FAB. The FAB hardness was measured and correlated to palladium distribution and grain structure. First bond process responses were characterized. The impact of palladium on wire bondability and wire bond intermetallic using a high temperature storage test was studied.